Ovarian hyperstimulation syndrome mimicking ovarian malignancy: a case report - Singh, Sujata; Swain, Sasmita; Das, Lucy; Das, Om Avishek; Sahoo, Balaram; Sahoo, Sasmita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Ovarian hyperstimulation syndrome (OHSS) is an iatrogenic complication. In most cases, the clinical manifestations of OHSS are self-limited and OHSS resolves spontaneously within a few days, provided that appropriate supportive measures are taken. However, OHSS has been associated with substantial morbidity, principally acute respiratory distress, and fatal complications have been reported in patients with severe or critical OHSS.